FLORID ECTOPIC CUSHING SYNDROME FROM AN UNRESECTABLE MEDIASTINAL NEUROENDOCRINE TUMOUR - Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd; Borhan, Marisa Khatijah; Alwi, Ahmad Naufal Md; Hassim, Norsyahinaz (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Ectopic adrenocorticotropic hormone (ACTH) Cushing syndrome (ECS) is rare but frequently a severe condition because of the intensity of hypercortisolism. Fifty percent of ECS originates primarily from neuroendocrine tumours (NETs) of the lung. NETs from the mediastinum are extremely rare; they often arise from the thymus gland or paraganglionic structures. CASE A 46-year-old male presented with altered behaviour and fatigue. On examination, the patient was hypertensive at 184/91 mm Hg, lean with a BMI of 23 kg/m² and with physical examination findings of hyperpigmented palmar crease, acanthosis nigricans, and generalised acne. Laboratory investigations revealed severe hypokalemia (1.6 mmol/L) and metabolic alkalosis (pH 7.755, HCO₃ 62.5). ODST was not suppressed (1519 nmol/L) and 24-hour urine cortisol was elevated at 16,198 nmol. ACTH was increased at 70.40 pmol/L (normal 1.6–13.9) and HbA1c was 5.1%. No pituitary adenoma was noted from the pituitary MRI. Whole-body CT reported an anterior mediastinal mass with the largest diameter at 9.2 cm and a T8 vertebrae compression fracture. Functional PET-CT showed predominant avidity in the FDG-PET compared to the Gallium-PET scan. CT-guided biopsy confirmed an intermediate-grade NET (atypical carcinoid). The mass was unresectable as it encased the great vessels. Oral ketoconazole was commenced to control his hypercortisolemic state and IM Octreotide LAR 30 mg four times weekly. He responded well; his repeat morning cortisol ranged between 252 and 327 nmol/L. Antihypertensives, ketoconazole, and potassium supplements were gradually titrated down. However, four months later, he was readmitted for symptomatic severe hypokalemia and raised cortisol level (1453 nmol/L). Repeat imaging showed progressive disease, now with metastasis to the lung, scapula and tumour thrombosis. Chemotherapy with Etoposide and Carboplatin was initiated. Unfortunately, the patient succumbed to sepsis after his second cycle of chemotherapy. CONCLUSION The primary treatment of ECS is surgical resection of the ACTH-secreting tumour. Other treatment options are chemotherapy, somatostatin analogues, and radiotherapy. Medical therapy with adrenal enzyme synthesis inhibitors may be needed to control the degree of hypercortisolemia.